Studies on minimal processing of pineabble - MANISH KUMAR JHA REEBA MARIAM JOSHUA VINEETHA M; Er. Prince M. V (Guide) (Tavanur 2005 Kelappaji College of Agricultural Engineering and Technology)
To develop a minimal processing method for pineapple titbis employing the hurdle concept. fabrication of an osmotic dehydration apparatus for dehydration of pineapple titbis . shelf life studies of pineapple titbis
Studies on minimal processing of pineabble